Low-concentration uranium enters the HepG2 cell nucleus rapidly and induces cell stress response. Issue 1 (25th December 2015) - Guéguen, Yann; Suhard, David; Poisson, Clémentine; Manens, Line; Elie, Christelle; Landon, Géraldine; Bouvier-Capely, Céline; Rouas, Caroline; Benderitter, Marc; Tessier, Christine
Abstract: This study aimed to compare the cell stress effects of low and high uranium concentrations and relate them to its localization, precipitate formation, and exposure time. The time-course analysis shows that uranium appears in cell nuclei as a soluble form within 5 min of exposure, and quickly induces expression of antioxidant and DNA repair genes. On the other hand, precipitate formations began at the very beginning of exposure at the 300-μM concentration, but took longer to appear at lower concentrations. Adaptive response might occur at low concentrations but are overwhelmed at high concentrations, especially when uranium precipitates are abundant. Highlights: SIMS is a new elemental imaging technique for uranium distribution in cells. Uranium enters cell nuclei very rapidly as a soluble form. Uranium quickly induces cell stress responses. Cell response leading to cell death is observed when uranium precipitates. Low-concentration uranium reinforces the antioxidant system.